« Je rêve de Catherine. Je suis Catherine » : le jeu des je narratifs dans La maison Trestler ou le 8e jour d’Amérique de Madeleine Ouellette-Michalska - Bujnowska, Ewelina (Romanica Silesiana)
In the present article, the author discusses literary games as exemplified by the novel La Maison Trestler ou le 8e jour d’Amérique by the Canadian writer Madeleine Ouellette-Michalska. The game that we are invited to play turns out to be complex because it occurs on many levels, particularly on the level of the narration. Ouellette-Michalska’s novel is based on a game played by multiple female identities, questioning the exclusively masculine point of view dominant in the historical discourse. Asking whether history is able to depict every aspect of an event truthfully, the novel allows the intrusion of memories and feelings into the presentation of the past. Suggesting “settling the score” between the male and female history, the writer reconsiders the question of historical truth. In her opinion, women’s memory partly escapes the male logic of space/time and facilitates the coming of the eighth day, the day of America. Key words: History/Herstory, women’s memory, historical truth.